Evaluation of a peer led parenting intervention for disruptive behaviour problems in children: community based randomised controlled trial. (13th March 2012) - Day, Crispin; Michelson, Daniel; Thomson, Stacey; Penney, Caroline; Draper, Lucy
Abstract : Objective To evaluate the effectiveness of a peer led parenting intervention delivered to socially disadvantaged families. Design Randomised controlled trial. Setting Schools and children's centres in a socially deprived borough of inner London. Participants Parental caregivers seeking help with managing the problem behaviours of 116 index children, aged 2-11 years; 59 families were randomised to the intervention and 57 to a waitlist control condition. Intervention Empowering parents, empowering communities is an eight week (two hours each week), manualised programme delivered to groups of parents by trained peer facilitators from the local community. Main outcome measures Child problems (number and severity), parental stress, and parenting competencies were assessed before and after the intervention using standardised parent reported measures. Results Significantly greater improvements in positive parenting practices and child problems were observed in the intervention group compared with the waitlist group, with no difference in parental stress between the groups. An intention to treat analysis for the primary outcome measure, the intensity subscale of the Eyberg child behaviour inventory, showed an intervention effect size of 0.38 (95% confidence interval 0.01 to 0.75, P=0.01). The intervention group had high rates of treatment retention (91.5%) and user satisfaction. Conclusion The peer led parenting intervention significantly reduced child behaviour problems and improved parenting competencies. This is a promising method for providing effective and acceptable parenting support to families considered hard to reach by mainstream services. Trial registration Current Controlled Trials ISRCTN01962337 .